Influence of Railway Control and Signaling Equipment on Reduction of Occurrences in the State Railway Network of Czech Republic - Seelmann, Herbert; Hromádka, Vít; Korytárová, Jana; Vítková, Eva; Funk, Tomáš (Elsevier, 2020)
The paper develops the issue of the evaluation of investment projects in the area of the national railway infrastructure solved within the research project. The research projects is focused on the evaluation of benefits connected with the increasing of the safety and the reliability of the railway infrastructure due to the realization of projects including investments into managing and security equipment. The paper is focused on the identification of the relation between the change of the level of security on the railway and the change of the number of occurrences on the railway. The methodology of the research consists in the analysis of the database of occurrences obtained from the sources of the Railway Infrastructure Administration, which includes approximately 1 000 occurrences annually per last ten years (2009 - 2018). The database includes detailed information about registered occurrences. The output of the partial part of the research is the identification of the relation between specific occurrence and its cause and the level of the security in the place of the origin of the occurrence. The results of the research will be consequently used for the evaluation of benefits connected with the increasing of the safety and the reliability of the railway. (C) 2020 The Authors. Published by Elsevier Ltd.

The paper develops the issue of the evaluation of investment projects in the area of the national railway infrastructure solved within the research project. The research projects is focused on the evaluation of benefits connected with the increasing of the safety and the reliability of the railway infrastructure due to the realization of projects including investments into managing and security equipment. The paper is focused on the identification of the relation between the change of the level of security on the railway and the change of the number of occurrences on the railway. The methodology of the research consists in the analysis of the database of occurrences obtained from the sources of the Railway Infrastructure Administration, which includes approximately 1 000 occurrences annually per last ten years (2009 - 2018). The database includes detailed information about registered occurrences. The output of the partial part of the research is the identification of the relation between specific occurrence and its cause and the level of the security in the place of the origin of the occurrence. The results of the research will be consequently used for the evaluation of benefits connected with the increasing of the safety and the reliability of the railway. (C) 2020 The Authors. Published by Elsevier Ltd.
Influence of Railway Control and Signaling Equipment on Reduction of Occurrences in the State Railway Network of Czech Republic
Keywords: Occurrences; Safety; Reliability; Evaluation of Benefits; Economic Analysis; Occurrences; Safety; Reliability; Evaluation of Benefits; Economic Analysis